The New Three-Dimensional Safety Approach for the Implementation of Process Safety Management (PSM) and Improving Safety Aspects for the Pharmaceutical Industry in India – An Overview - Kumar, Alavandar Yudhistra (CV. Literasi Indonesia, 2024)
Implementation of the fourteen elements of process safety management (PSM) helps to build a good safety culture in the organization. The new three-dimensional approach, which consists of good safety practices, safety precautions, and frequent checking of the process equipment and its devices has been applied to the various elements of the process safety management. The elements of process safety management are six, four, and three are good safety practices, safety precautions, and frequent checking of process equipment and its devices but one of the elements is the combination of all the three-dimensional approach, which is a trade secret, which insists that all the people in the organization should follow all the documented procedures from two to thirteen elements of the process safety management, the controlled copy should only be used inside the company premises. We have taken secondary published data for assessing the deviations of the three-dimensional safety approach for the human failures in the pharmaceutical industry, which has led to various incidents/accidents from October 2017 to September 2021. The deviation, which we have observed for the good safety practices, safety precautions, and frequent checking of process equipment and its devices was ten, nine, and one numbers before implementation of the process safety management. After the implantation of the process safety management, the incidents were reduced to three numbers from January 2022 to August 2023, in which deviation has been found in the two and one for the good safety practices and safety precautions.